Eksistensi Tradisi Islam di Tengah Modernitas Perspektif Seyyed Hossein Nasr - Nurahyan (UIN Syarif Hidayatullah Jakarta), Muhammad Faiz (Paradigma: Jurnal Kalam dan Filsafat, 2024)
In today's modern era, humanity is faced with rapid advancements in technology and information. The ease of access allows people to obtain information quickly from one place to another. One of the characteristics of modern times is the shift in human understanding from a theocentric to an anthropocentric worldview. By prioritizing rationalism, empiricism, and materialism, modern humans have become the center or axis of life. According to Nasr, modernity is a condition in which humans exist outside the center of reality. Nasr also explains the problems of modernity caused by the modern worldview that places humans at the center of reality. The shift from a theocentric to an anthropocentric perspective is the main cause of the problems of modernity. The impacts of these problems include a spiritual crisis, an environmental crisis, and a civilizational crisis. The Islamic tradition presented by Nasr serves as a solution to these problems by reintroducing Islamic teachings from the classical era to the present, and comparing them with modern understandings from their origins to the present. This aims to clarify how these teachings can be applied in life so that worldly life may proceed better than before.